400 years of Dutch-Sri Lanka relations, 1602-2002 - Kelegama, Saman; Madawela, Roshan; Institute of Policy Studies (Colombo, Sri Lanka) (Colombo : Institute of Policy Studies of Sri Lanka, 2002)
Contributed articles.
Includes bibliographical references.
Keywords: Sri Lanka -- Foreign relations -- Netherlands; Netherlands -- Foreign relations -- Sri Lanka